GENERATION AS CULTURAL IDENTITY: THE DYNAMICS OF HISTORICAL EXPERIENCE IN THE FORMATION OF A SOCIETY’S SOCIAL CHARACTER - Salsabila Nurbaity; Aisyah Nur Fadhilah; Mirna Nur Alia Abdullah (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
A generation is understood not only as an age category, but also as a cultural identity shaped by the social and historical experiences collectively shared by individuals over a specific period of time. This article aims to analyze how the dynamics of historical experiences play a role in shaping the social character and value systems of each generation in society. This study employs a qualitative approach through a literature review of various sociological studies on the concept of generation and social change. The findings indicate that historical events, technological developments, and social and cultural changes influence a generation’s mindset, value orientation, and lifestyle. Each generation subsequently develops distinctive social characteristics in response to the context of its time. In contemporary society, the acceleration of globalization and digitalization further strengthens the process of generational identity formation through increasingly widespread social interactions. Therefore, understanding generations as cultural identities is crucial for examining the dynamics of social change and intergenerational relationships in modern society.